Identifying opportunities for transboundary conservation in Africa - Kamath, Vignesh; Brooks, Holly; Naidoo, Robin; Brennan, Angela; Bertzky, Bastian; Burgess, Neil D.; McDermott Long, Osgur; Arnell, Andy; Bhola, Nina (Frontiers in Conservation Science, 2023)
The conservation of natural and cultural resources shared between countries is a significant challenge that can be addressed through the establishment of transboundary conservation areas (TBCAs). TBCAs enable countries to harmonize cross-border governance and management, increase protected area (PA) coverage, and strengthen relationships between neighbouring countries and communities. In Africa, many ecosystems and species ranges span multiple countries, making TBCAs a crucial tool for biodiversity conservation.However, there is a lack of research on where TBCAs can be established or need to be established. To address this gap, we conducted a study to identify opportunities for establishing TBCAs in Africa. We first compiled an up-to-date list of existing TBCAs on the continent. Then, we identified potential TBCAs by identifying protected areas next to country borders that are adjacent to other protected areas in a neighbouring country. We also evaluated the functional connectivity between these PA pairs and prioritized potential TBCAs based on size, connectivity, and ease of establishment. Our results provide a baseline of existing TBCAs and offer a better understanding of where transboundary conservation might be established or strengthened. We also highlight areas where future transboundary conservation efforts could safeguard PA connectivity. This information can guide policy and Style Definition: Heading 2 Style Definition: Heading 1 decision-making processes towards promoting conservation and sustainable use of natural and cultural resources shared between countries in Africa.